Analisis Terhadap Pemahaman Hadis Nabi Musa Menampar Malaikat Maut - Zakiyah, Zakiyah; Putra, Alven (Institut Agama Islam Sumatera Barat Pariaman, 2024)
The hadith about the Prophet Moses slapping the Angel of Death has caused controversy among scholars. Although this hadith has a valid sanad and is narrated by a reliable narrator, some scholars argue that its text contains impossibilities and cannot be accepted by reason. This study aims to analyze the various understandings of scholars regarding the hadith of the Prophet Moses slapping the Angel of Death and to find a middle ground to understand it. The method used in this study is qualitative with a library research approach. The results of the study show that the hadith does not contain impossibilities and does not contradict human reason and logic. Differences in views in understanding this hadith do not damage a person's faith, especially since this hadith is not directly related to faith or sharia. However, it should be noted that when faced with a hadith that seems to contradict logic, it is best not to rush to declare the hadith weak, because something that seems to contradict logic to some people may not be so to others.